Computational Prediction of Ammonia-Borane Dehydrocoupling and Transfer Hydrogenation of Ketones and Imines Catalyzed by SCS Nickel Pincer Complexes - Qiu, Bing; Wang, Wan; Yang, Xinzheng (Frontiers in Chemistry, 2019)
Inspired by the active site structure and catalytic mechanism of lactate racemase, three scorpion-like SCS nickel pincer complexes were proposed as potential catalysts for transfer hydrogenation of ketones and imines with ammonia-borane (AB) as the hydrogen source. Density functional theory calculations reveal a stepwise proton and hydride transfer mechanism for the dehydrocoupling of AB and hydrogenation of N-methylacetonimine, and a concerted proton-coupled hydride transfer process for hydrogenation of acetone, acetophenone, and 3-methyl-2-butanone. Among all proposed Ni complexes, the one with symmetric NH2 group on both arms of the SCS pincer ligand is the most active one with free energy barriers of 15.0 kcal/mol for dehydrogenation of AB, as well as 17.8, 18.2, 18.0, and 18.6 kcal/mol for hydrogenation of acetone, N-methylacetonimine, acetophenone, and 3-methyl-2-butanone, respectively.